Star polymer/water solutions: new experimental findings - Branca, C.; Magaz, S.; Migliardo, F. (Condensed Matter Physics, 2002)
The purpose of the present work is to highlight a number of recent experimental results that have contributed significantly to the research area of star polymer. Firstly we will refer to a very impressive SANS work by J.Peyrelasse, C.Perreur, J.-P.Habas and J.Franc¸ois which is focused on the study of the structural properties of aqueous solutions of a star copolymer of PEO and PPO by Small Angle Neutron Scattering. Next, we will refer to some experimental advances reported in the work by R.Triolo, V.Arrighi, A.Triolo, P.Migliardo, S.Magaz`u, J.B.McClain, D.Betts, J.M.DeSimone, H.D.Middendorf, which deals with a study of some dynamical properties of PS-b-PFOA aggregates in supercritical CO₂ by Quasi Elastic Neutron Scattering.